KAJIAN EKSPERIMENTAL PERILAKU MEKANIS BETON BERSERAT BAJA TIPE HAREX - Kurniawandy, Alex
The thesis deals with experimental investigation of the effects of the including of compressive strenght, tensile strenght, rupture of modulus and toughness index was undertaken to study the behavior of concrete with addition HAREX steel fiber. Characteristics of HAREX steel fibers have longitudinal twisting and end hooks. Seventy-two concrete cylinders and twelve concrete beams were made with typical dimension. Eighteen of cylinders and three of beams were made of plain concrete and the other cylinders and beams were made of steel fiber reinforced concrete with different fiber content. The addition of steel fibers to normal strength concrete provides a significant increase in compression strength, splitting tensile strength and flexure strength. The increase content of steel fiber makes value of compression; splitting tensile and flexure strength increase too. The increases in flexural strength are higher than increases in either compressive or tensile strength. From Stress - strain behavior, the additions of steel fibers increase the strain at peak load. The beam under flexure reaches small crack, steel fibers bridging the matrix so that matrix is not failure immediately. An increase in fiber content results in consistent increase in toughness index. All of the result investigation .